Antifungal Activity of Rosmarinus Officinalis Essential Oil and Nystatin on Store Isolate of Candida species from HIV/AIDS Patients with Oral Candidiasis - Bernadya Yogatri Anjuwita; Iskandar Zulkarnain; Muhammad Yulianto Listiawan; Evy Ervianti; Rahmadewi Rahmadewi; Pepy Dwi Endraswari; Damayanti Damayanti; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Oral candidiasis is caused by the mycotic activity of Candida albicans present in the oral cavity, and it is one of the most common opportunistic infections found in patients with Human Immunodeficiency Virus (HIV)/acquired immune deficiency syndrome (AIDS). The growing resistance and side effects to common antifungal drugs have promoted herbal essential oils as antifungal agents in recent years. In this study, essential oils (EO) of Rosmarinus officinalis (Lamiaceae) were examined for in vitro antifungal activity against Candida species. Purpose: To evaluate the antifungal activity of essential oils of Rosmarinus officinalis (Lamiaceae) and nystatin using the microdilution technique by determining the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) of Candida spesies. Methods: This was an experimental laboratory study with a post-test-only design conducted in Dr. Soetomo General Academic Teaching Hospital, Surabaya. Forty isolates consisted of twenty isolates of Candida albicans and twenty isolates of Candida non-albicans were collected. The isolates were tested for antifungal activity using the microdilution on 96-well plates. Result: There was a significant difference from the results of the MIC concentration of rosemary essential 100% to 6.25% microdilution method between nystatin and rosemary essential oil (p < 0.05). Conclusion: The antifungal activity of rosemary essential oil was better than nystatin that the lowest MIC value, which was 6.25%, has been obtained the microdilution method. The minimum fungicidal concentration of rosemary essential oil was 25%, while the minimum fungicidal concentration nystatin was higher than 100%.